Peningkatan Potensi Ekonomi Melalui Program Pemeliharaan Lingkungan Desa Dan Pemberdayaan Bank Sampah Desa Pamagersari - Sri Mulyantini; Aniek Irawatie (IKRA-ITH ABDIMAS, 2023)
This village environmental maintenance program aims to raise public awareness of the creationof a healthy environment while providing economic benefits for the community. This activity iscarried out by integrating the environmental village program with economic empowerment fromexisting waste banks, based on the 4R (Reduce, Reuse, Recycle, Replace) program for thePamagersari Village community to support the development of the Lebak Wangi tourist village.This program involves neighborhood associations (RT) and neighborhood associations (RW),environmental groups. This program will also involve existing Educational Institutions, such asSchools and Islamic Boarding Schools as well as SME groups. We hope that this program cansupport government programs in environmental care as well as extracting and developing villagepotential.